The (surprising?) nonchalance of migration control agents. - Eule, Tobias G. (Journal of Ethnic & Migration Studies, 2018)
This paper sheds light onto the processes of controlling irregular migration in Germany, based on ethnographic fieldwork with immigration officials, police forces, home office bureaucrats and non-state actors. Several studies have examined the policies and tools of migration control available to state officials and contracted third parties and generally found a trend towards greater restrictiveness and securitisation with regard to irregular migration. However, relatively few analyse their actual implementation. This paper seeks to fill this gap, and to act as slight corrective by highlighting the relatively limited nature by which migration control was exercised. In fact, the practice of detecting, identifying, detaining and deporting irregular immigrants was far removed from the politicised discourse that surrounds it in the public sphere and academia, and instead influenced by pragmatism and nonchalance. However, in contrast to explanations that see lenience towards irregular migrants as motivated by economic factors, here the limits of migration control were directly related to officials’ sense of duty, as well as working conditions and a lack of institutional oversight. In this sense, the enhanced possibilities of control through new means of surveillance and data collection are in fact restricted because officials might just not be bothered to use them.